2021
DOI: 10.1002/ejic.202100529
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides

Abstract: Reaction of [( DIPeP BDI)SrH] 2 with C 6 H 5 X (X = Cl, Br, I) led to hydride-halogenide exchange ( DIPeP BDI = HC[(Me) phenyl] 2 ). Conversion rates increase with increasing halogen size (F < Cl < Br < I). Reaction of [( DIPeP BDI)SrH] 2 with C 6 H 5 F was slow and ill-defined but addition of C 6 H 4 F 2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [( DIPeP BDI)SrX • THF] 2 (X = F, Cl, Br, I). Mixtures of AeN" 2 and PhSiH 3 in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…The dihedral angles between the Ca 2 X 2 and N 2 Ca planes gradually decrease descending the halogen group: F 74.1(1)°>Cl 64.2(1)°>Br 24.0(1)°>I 8.5(1)° (Figure 2b). Although the same trend was also observed in a series of comparable Sr halogenide complexes, [( DIPeP BDI)SrX ⋅ (THF)] 2 (X=F, Cl, Br, I), [30] we have currently no clear‐cut explanation for these geometric changes. The metal coordination spheres are governed by electrostatic and steric repulsion between ligands, as is generally the case for highly ionic s ‐block metal complexes.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…The dihedral angles between the Ca 2 X 2 and N 2 Ca planes gradually decrease descending the halogen group: F 74.1(1)°>Cl 64.2(1)°>Br 24.0(1)°>I 8.5(1)° (Figure 2b). Although the same trend was also observed in a series of comparable Sr halogenide complexes, [( DIPeP BDI)SrX ⋅ (THF)] 2 (X=F, Cl, Br, I), [30] we have currently no clear‐cut explanation for these geometric changes. The metal coordination spheres are governed by electrostatic and steric repulsion between ligands, as is generally the case for highly ionic s ‐block metal complexes.…”
Section: Resultssupporting
confidence: 62%
“…The latter were obtained by hydrodehalogenation of PhX with [( DIPeP BDI)SrH] 2 . This direct X − /H − exchange likely follows a c S N Ar mechanism [30] . Based on formation of biphenyl, we propose a similar nucleophilic mechanism for the reaction of VIII with PhX (Scheme 2).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…They found that the conversion rate increases with the metal size (Ca < Sr < Ba) and halogen size (F < Cl < Br < I). 34 Herein, using (CAAC) 2 Be, NtBuNtBuBe…”
Section: Introductionmentioning
confidence: 99%